FIRST RECORD OF THE JEWEL BEETLE FIRST RECORD OF THE JEWEL BEETLE FIRST RECORD OF THE JEWEL BEETLE Sternocera Sternocera Sternocera Spp. (Coleoptera: (Coleoptera: buprestidae) ON buprestidae) ON buprestidae) ON ACACIA SENEGAL IN JODHPUR - LOKENDRA SINGH RATHORE, BUNDESH KUMAR; GEETA VISHNOI, SHIWANI BHATNAGAR, AMEEN ULLAH KHAN (The Bioscan, 2018)
The jewel beetle species Sternocera spp. has been recorded on Acacia senegal in Jodhpur for the first time. The beetles were collected on Acacia senegal trees at Kalyana Kumathiya enclosure Jodhpur feeding on foliage of the tree. It is large metallic wood boring beetle within the family Buprestidae. Its pronotum is metallic green in colour and elytra is coppery-brown. These are wood-boring in larvae stages, slowly tunneling through woody tissues of trees.